Kynurenine 3-Monooxygenase: An Influential Mediator of Neuropathology - Parrott, Jennifer M.; O’Connor, Jason C. (Frontiers in Psychiatry, 2015)
Mounting evidence demonstrates that kynurenine metabolism may play an important pathogenic role in the development of multiple neurological and neuropsychiatric disorders. The kynurenine pathway consists of two functionally distinct branches that generate both neuroactive and oxidatively reactive metabolites. In the brain, the rate-limiting enzyme for one of these branches, kynurenine 3-monooxygenase (KMO), is predominantly expressed in microglia and has emerged as a pivotal point of metabolic regulation. KMO substrate and expression levels are up-regulated by pro-inflammatory cytokines and altered by functional genetic mutations. Increased KMO metabolism results in the formation of metabolites that activate glutamate receptors and elevate oxidative stress, while recent evidence has revealed neurodevelopmental consequences of reduced KMO activity. Together, the evidence suggests that KMO is positioned at a critical metabolic junction to influence the development or trajectory of a myriad of neurological diseases. Understanding the mechanism(s) by which alterations in KMO activity are able to impair neuronal function and viability will enhance our knowledge of related disease pathology and provide insight into novel therapeutic opportunities. This review will discuss the influence of KMO on brain kynurenine metabolism and the current understanding of molecular mechanisms by which altered KMO activity may contribute to neurodevelopment, neurodegenerative and neuropsychiatric diseases.